Participatory Decision Making: A Field Experiment on Manipulating the Votes - Paolo Spada; Raymond Vreeland (Economics and Econometrics Research Institute (EERI), 2010)
Many believe that deliberative democracy, where individuals discuss alternatives before voting on them, should result in collectively superior outcomes because voters become better informed and decisions are justified using reason. These deliberations typically involve a moderator, however, whose role has been under-examined. We conduct a field experiment to test the effects moderators may have. Participants in a class of 107 students voted on options over their writing and exam requirements. Before voting, they participated in group discussions of about five people each with one moderator. Some (randomly assigned) moderators remained neutral throughout, while others made limited interventions, supporting a specific option. We find a substantial moderator effect. Our experiment is structured like deliberations used world-wide to make community decisions and thus should have some external validity. The results indicate that if organized interest groups had influence over moderators, they might be able to hijack a deliberative decision-making process.
Keywords: G10; G30; G34; G38; K20; K22; 330; Participatory Decision Making; Field Experiment; Voting